PROFIL PEMAHAMAN MODEL PEMBELAJARAN OLEH GURU KIMIA SMA NEGERI SE-KOTA BENGKULU - Bella Hani Anggita; Elvinawati Elvinawati; Hermansyah Amir (ALOTROP, 2026)
This study aims to describe the level of understanding of learning models by chemistry teachers of public high schools in Bengkulu City with a descriptive research type using a quantitative approach survey method. The sample in this study were all chemistry teachers of public high schools in Bengkulu City and was conducted from June to September 2025 using a closed questionnaire as the research instrument. The results showed that the level of understanding of learning models by chemistry teachers of public high schools in Bengkulu City was in the moderate category with an average score of 85.03, this indicates that chemistry teachers have understood the basic concepts of learning models quite well, but the understanding is not yet in-depth in every sub-aspect of the learning process. This condition shows that chemistry teachers still need reinforcement in understanding learning models so that their implementation in the classroom can take place more optimally.   Keywords: Learning model, Level of Understanding, Chemistry teacher